2015
DOI: 10.1007/s11356-015-5014-5
|View full text |Cite
|
Sign up to set email alerts
|

Malathion-induced hepatotoxicity in male Wistar rats: biochemical and histopathological studies

Abstract: The increasing use of organophosphorus pesticides in the environment constitutes an ecotoxicological hazard especially for humans and non-target animals. Hereby, we analyzed the toxic effects of malathion on the histological structure of liver and biochemical parameters in male rats. Three groups received daily different amounts of malathion: 1/1000, 1/100, and 1/10 LD50 for 30 days. The weights of treated rat's liver have increased. Analyzed tissues showed centrilobular and sinusoidal congestion, hepatocyte h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…In the meantime, hepatocyte necrosis in a small lesion with a little of inflammatory cell infiltration in the middle-dose group, as well as edema of hepatocytes in the high-dose group were observed. Similar results had been reported in 2 cases of drug-induced hepatic injury (DILI) (28) and some hepatotoxicity studies of MLT, including histopathological and hematological changes (29)(30)(31). In addition to that, the absolute and relative weights of liver in the high-dose group were increased, which might be induced by the metabolism of MLT.…”
Section: Discussionsupporting
confidence: 85%
“…In the meantime, hepatocyte necrosis in a small lesion with a little of inflammatory cell infiltration in the middle-dose group, as well as edema of hepatocytes in the high-dose group were observed. Similar results had been reported in 2 cases of drug-induced hepatic injury (DILI) (28) and some hepatotoxicity studies of MLT, including histopathological and hematological changes (29)(30)(31). In addition to that, the absolute and relative weights of liver in the high-dose group were increased, which might be induced by the metabolism of MLT.…”
Section: Discussionsupporting
confidence: 85%
“…Many environmental chemicals pose a threat to the liver . We found that cis ‐BF exposure caused areas with balloon‐like changes and immune cell infiltration in the liver (Figure ), implying that oral exposure to cis ‐BF may lead to liver damage.…”
Section: Discussionmentioning
confidence: 84%
“…They found that MAL treatment leads to enhanced production of reactive oxygen species (ROS) and subsequent lipid peroxidation (Durak et al 2009;Bhardwaj et al 2018). It is evident that lipid peroxidation is accompanied by an alteration, either inhibition or activation, of the antioxidant defense system in different organs (Flehi-Slim et al 2015). Different studies revealed that MAL decreased the activity of cellular antioxidant defenses, superoxide dismutase (SOD), reduced glutathione (GSH), and glutathione peroxidase (GPx), thus disrupting the oxidantantioxidant balance in the body (Akhgari et al 2003;Franco et al 2009;Ozsoy et al 2016;Ullah et al 2018;Thakur et al 2018).…”
Section: Pharmacodynamics Of Malathionmentioning
confidence: 99%